Novel word retention in bilingual and monolingual speakers - Kan, Pui Fong; Sadagopan, Neeraja (Frontiers in Psychology, 2014)
The goal of this research was to examine word retention in bilinguals and monolinguals. Long-term word retention is an essential part of vocabulary learning. Previous studies have documented that bilinguals outperform monolinguals in terms of retrieving newly-exposed words. Yet, little is known about whether or to what extent bilinguals are different from monolinguals in word retention. Participants were 30 English-speaking monolingual adults and 30 bilingual adults who speak Spanish as a home language and learned English as a second language during childhood. In a previous study (Kan, Sadagopan, Janich, & Andrade, 2014), the participants were exposed to the target novel words in English, Spanish, and Cantonese. In this current study, word retention was measured a week after the fast mapping task. No exposures were given during the one-week interval. Results showed that bilinguals and monolinguals retain a similar number of words. However, participants produced more words in English than in either Spanish or Cantonese. Correlation analyses revealed that language knowledge plays a role in the relationships between fast mapping and word retention. Specifically, within- and across-language relationships between bilinguals’ fast mapping and word retention were found in Spanish and English, by contrast, within-language relationships between monolinguals’ fast mapping and word retention were found in English and across-language relationships between their fast mapping and word retention performance in English and Cantonese. Similarly, bilinguals differed from monolinguals in the relationships among the word retention scores in three languages. Significant correlations were found among bilinguals’ retention scores. However, no such correlations were found among monolinguals’ retention scores. The overall findings suggest that bilinguals’ language experience and language knowledge most likely contribute to how they learn and retain new words.